Simulating Solar Neighborhood Brown Dwarfs. I. The Luminosity Function above and below the Galactic Plane - Easton J. Honaker; John E. Gizis (The Astrophysical Journal)
Brown dwarfs form the key, yet poorly understood, link between stellar and planetary astrophysics. These objects offer unique tests of Galactic structure, but observational limitations have inhibited their large-scale analysis to date. Major upcoming sky surveys will reveal unprecedented numbers of brown dwarfs, among even greater numbers of stellar objects, greatly enhancing the statistical study of brown dwarfs. To extract the comparatively rare brown dwarfs from these massive data sets, we must understand the parameter space they will occupy. In this work, we construct synthetic populations of brown dwarfs in the solar neighborhood to explore their evolutionary properties using Gaia-derived star formation histories alongside observational mass, metallicity, and age relationships. We apply the Sonora Bobcat, Saumon−Marley, and Sonora Diamondback evolutionary models. From the populations, we explore the space densities and median ages by spectral type. We present the simulated luminosity function and its evolution with distance from the Galactic plane. Our simulation shows that brown dwarf population statistics are a function of height above/below the Galactic plane and sample different age distributions. Interpreting the local sample requires combining evolutionary models, the initial mass function, the star formation history, and kinematic heating. Our models are a guide to how well height-dependent samples can test these scenarios. Subpopulations of brown dwarfs farther from the Galactic plane are older and occupy a different region of parameter space than younger subpopulations closer to the Galactic plane. Therefore, fully exploring population statistics both near and far from the Galactic plane is critical to prepare for upcoming surveys.